2017
DOI: 10.5858/arpa.2017-0114-sa
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-Site Evaluation of Endobronchial Ultrasound–Guided Transbronchial Needle Aspirations for the Diagnosis of Lung Cancer: A Perspective From Members of the Pulmonary Pathology Society

Abstract: - Rapid on-site evaluation can ensure that the targeted lesion is being sampled and can enable appropriate specimen triage. If available, it should be used with EBUS-TBNA in the diagnosis of lung cancer because it can minimize repeat procedures for additional desired testing (ie, molecular studies). Some studies have shown that ROSE does not adversely affect the number of aspirations, total procedure time of EBUS-TBNA, or the rate of postprocedure complications; it is also helpful in providing a preliminary di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
164
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(173 citation statements)
references
References 72 publications
3
164
0
6
Order By: Relevance
“…Sample material was extruded using the needle stylet and an air-filled syringe into a saline pot for FFPE cell block. The last drops were blown onto one slide for Diff-Quik [10] and onto another slide for immediate fixation and subsequent PAP staining. The pathologist supervised the making of the Diff-Quik smears (hereafter called “smears”) and ensured that the smallest possible drop of material went onto the slide so as not to impair smear quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample material was extruded using the needle stylet and an air-filled syringe into a saline pot for FFPE cell block. The last drops were blown onto one slide for Diff-Quik [10] and onto another slide for immediate fixation and subsequent PAP staining. The pathologist supervised the making of the Diff-Quik smears (hereafter called “smears”) and ensured that the smallest possible drop of material went onto the slide so as not to impair smear quality.…”
Section: Methodsmentioning
confidence: 99%
“…Mediastinal and hilar nodes can be easily sampled using EBUS-TBNA with few side effects and a 95% sensitivity for diagnosing malignancy [5, 7-9]. The EBUS-TBNA procedure can be accompanied by rapid on-site evaluation (ROSE) of sample material, using air-dried and Diff-Quik-stained cytology smears to provide immediate feedback for the proceduralist [10-12]. The remainder of the material is utilised for Papanicolaou (PAP) stains and for the preparation of a formalin-fixed paraffin-embedded (FFPE) cell block, which is important for formal diagnostic analysis, immunohistochemical staining, and molecular testing [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the widespread implementation of this form of evaluation is hampered by a number of factors [1-4]. First, randomized trials and meta-analyses have clearly demonstrated that ROSE does not increase the diagnostic yield or the specimen adequacy of conventional transbronchial needle aspiration (c-TBNA) or endosonography-derived samples from lymphadenopathy [5-11].…”
Section: Introductionmentioning
confidence: 99%
“…It may also improve the rate of successful molecular profiling in patients with advanced lung cancer [8] and may optimize the triage of the specimen for ancillary studies [1, 18], alongside improving the utilization of laboratory and health care resources [19]. …”
Section: Introductionmentioning
confidence: 99%
“…The major limitation of our study is that we have utilized small biopsies as the comparison standard for histology. In practice, clinicians frequently perform cytology aspirates (with or without cell blocks) and endobronchial/transbronchial biopsies in the same clinical procedure to improve diagnostic yield . Hence, we reasoned that the histology on small biopsies will be fairly representative of cytomorphology for comparison purposes in most cases.…”
Section: Discussionmentioning
confidence: 99%